Lived Experiences of Adolescent Living with human immunodeficiency virus in Ghana: A Phenomenology Study - Abdul‐Razak Doat; Elham Navab; Akram Sadat Sadat Hoseini (Wiley, 2021)
Abstract Aim and objectives To explore the meaning of living with HIV positive in Ghanaian adolescents. Design Hermeneutic phenomenological approach developed by Van Manen methodology (1990). Method A purposive sampling of 12 adolescents living with HIV was recruited. Data were collected between September 2019-January 2020 using semi‐structured interviews and analysed using thematic analysis. Results Two main themes emerged: Stigmatization and HIV disclosure and Living with a heavy burden. Seven subthemes were also found. Adolescents living with HIV in Ghana face discrimination, rejection and go through psychological distress such as suicidal thoughts, fear of death and hopelessness. Conclusion The problems faced by adolescents living with HIV are a result of the inherent beliefs of the Ghanaian society about HIV. Nurses working with ADLHIV should concentrate on identifying challenges and provide support and care, in addition to their treatment.